2016
DOI: 10.1136/bcr-2016-216133
|View full text |Cite
|
Sign up to set email alerts
|

Orolingual angioedema to alteplase. Identify, counsel and monitor at risk patients

Abstract: Orolingual angioedema (OLA) is a known complication of intravenous alteplase used to treat ischaemic stroke. The incidence may be as high as 5.1%. ACE inhibitors are thought to increase the risk of developing this potentially life-threatening complication. This case report demonstrates how we may improve in the identification of risk factors in the history; the counselling of patients appropriately; in seeking alternative therapies such as mechanical thrombectomy; and in the monitoring of patients for signs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…With a small population that developed severe angioedema, it is difficult to make comparisons between this group and the patients who did not develop angioedema. Lastly, to be included in this study, the patient had to have received tPA for suspected CVA as opposed to confirmed CVAs used in other studies reviewed [ 1 4 , 6 , 7 , 9 , 10 , 13 , 17 ]. As stated previously, cerebral ischemia increases the amount of B2 bradykinin receptors in the brain which can increase the risk of developing angioedema with tPA, but it is unclear if this increase in receptors occurs only in ischemic CVAs or in transient ischemic accidents (TIAs) as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a small population that developed severe angioedema, it is difficult to make comparisons between this group and the patients who did not develop angioedema. Lastly, to be included in this study, the patient had to have received tPA for suspected CVA as opposed to confirmed CVAs used in other studies reviewed [ 1 4 , 6 , 7 , 9 , 10 , 13 , 17 ]. As stated previously, cerebral ischemia increases the amount of B2 bradykinin receptors in the brain which can increase the risk of developing angioedema with tPA, but it is unclear if this increase in receptors occurs only in ischemic CVAs or in transient ischemic accidents (TIAs) as well.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinin B2 receptors are upregulated in dying neurons such as that seen in ischemic CVA [ 1 ]. Angiotensin-converting enzyme (ACE) inhibitors prevent bradykinin degradation allowing for accumulation of bradykinin that can cause angioedema, and it is well known that ACE inhibitor use is associated with a higher risk of developing angioedema with tPA administration [ 1 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first argument for a pivotal role for bradykinin is the clinical observation that the type 2 bradykinin receptor antagonist icatibant and C1 inhibitor concentrate are highly effective in patients with r-tPA-induced angioedema, contrasting sharply the described effects of antihistamines, epinephrine, and steroids. [8][9][10][11][12][13][14] prestroke use of angiotensin-converting enzyme (ACE) inhibitors significantly increases the risk of developing r-tPA-induced angioedema in response to r-tPA therapy. 3,15,16 ACE degrades systemic bradykinin and SP, supported by other bradykinin metabolic enzymes such as aminopeptidase P, dipeptidyl-peptidase IV, neural endopeptidase, and carboxypeptidase N (Figure).…”
Section: Solitary Angioedema In Patients Treated With Recombinant Tis...mentioning
confidence: 99%